Buku Teks Bahasa Indonesia untuk Penutur Asing (BIPA): Tantangan Mempersiapkan Siswa di Dunia Kerja - Liana Kosasih; Robertus Pujo Leksono (Nuances of Indonesian Language, 2021)
Education system in Industrial Revolution 4.0 is being challenged to prepare students to be wellequipped with the 21st century skills.In addition to thiscompetitive globalization era, teaching of Bahasa Indonesia as a foreign language has come to the need of conformity of learning material to the working world. This paper will describe the impacts of “Sahabatku Indonesia - BIPA diplomacy material for Thai speaker” textbook to students of year 1 in Naresuan University. The use of learner-centred and teacher-friendly language textbook is still in debate among language teachers, publishers, as well as ministries of education across the globe (Tomlinson, 2012). The finding does not show the relation of learning material in text books to the needs in the working world, however, the findings describe the effectiveness of topical units in the text book that help students to acquire better understanding to the language, Indonesian people and culture, and arouse students’ interests to learn further studies of Indonesia and Bahasa Indonesia, which then in turns will be beneficial forthem in their working world.